Current and emerging two-drug approaches for HIV-1 therapy in ART-naïve and ART-experienced, virologically suppressed patients. (3rd May 2018) - Rossetti, Barbara; Montagnani, Francesca; De Luca, Andrea
ABSTRACT: Introduction : Current guidelines recommend a 2-drug antiretroviral regimen as an alternative to triple antiretroviral therapy (ART) in selected patients to reduce long-term toxicity and costs. Areas covered : This review is intended to provide insight into the efficacy, safety and tolerability of 2-drug versus 3-drug ART in naïve and in treatment-experienced virologically-suppressed patients. Expert opinion : Dual therapy regimens are not feasible in HBV-coinfected individuals and should not be applied during pregnancy. Positive data on 2-drug ART in drug naïve patients are still limited, while, in virologically-suppressed individuals, several regimens have shown non-inferiority as compared to 3-drug regimens. The strongest evidence of efficacy applies to ritonavir-boosted PI regimens combined with lamivudine and to dolutegravir with rilpivirine. Dual therapies showed improved renal function and bone mineral density over tenofovir disoproxil fumarate-based 3-drug regimens. There are also great expectations for ongoing phase 3 trials testing dolutegravir with lamivudine. New and future single tablet co-formulations of dual regimens are expected to improve their suitability. Despite the lack of comparison with tenofovir alafenamide-based 3-drug regimens, the 2-drug regimens showing consistent non-inferiority and safety versus 3-drug regimens will challenge the current paradigm of 3-drug ART.